ACCOUNTING IN A MULTIGENERATIONAL WORKPLACE: UNDERSTANDING VARIATIONS IN WORK BEHAVIOR - Johnson , David S; Thompson, Jessica L (Ayden International Journal of Applied Economics, Finance and Accounting, 2025)
Recruiting and retaining qualified certified public accountants (CPAs) is essential for organizations' fiscal management and success. The accounting profession is expected to grow significantly, increasing the pressure on businesses to hire CPAs whose work styles align with the evolving demands of the field. Traditionally, personality inventories have been used to assess candidates' fit with companies and positions, but these tools often overlook work styles. In high-demand, high-turnover professions like accounting, it is crucial to find accountants whose work styles align with the competencies needed for the role. This paper explores the changing landscape of the accounting profession, focusing on the competencies required for success in the 21st century, and discusses the importance of aligning work styles with these competencies.